2007
DOI: 10.1007/s10734-005-2464-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in academic performance in a large public university in Turkey

Abstract: The paper attempts to determine whether there are significant gender differences in academic performance among undergraduate students in a large public university in Turkey based on three indicators; university entrance scores, performance in the English preparatory school and in the program the student is majoring in. The paper finds that a smaller number of female students manage to enter the university and when they do so, they enter with lower scores. However, once they are admitted to the university, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 26 publications
(25 reference statements)
10
62
4
3
Order By: Relevance
“…While these variables are significant in some studies, as shown by Allen and Haniff (1991) or Dayioğlu and Türüt-Aşik (2007), in other contributions the results are inconclusive (Hoskins et al 1997;Smith and Naylor 2001). In consequence, more future research is therefore needed to monitor how gender and age may influence these relationships (Thomas 2000;Smith and Peterson 2007).…”
Section: Regression Resultsmentioning
confidence: 93%
“…While these variables are significant in some studies, as shown by Allen and Haniff (1991) or Dayioğlu and Türüt-Aşik (2007), in other contributions the results are inconclusive (Hoskins et al 1997;Smith and Naylor 2001). In consequence, more future research is therefore needed to monitor how gender and age may influence these relationships (Thomas 2000;Smith and Peterson 2007).…”
Section: Regression Resultsmentioning
confidence: 93%
“…Economic, social and cultural factors also have an important role to play in determining academic performance at an undergraduate level. However, the socio-economic factors that affected one's performance at an undergraduate level (in the above studies [3][4][5][6][7][8][9][10][11][12] ) may not be as strongly pronounced for an honours degree. Nevertheless, including these factors as covariates in our prediction model will be important for the analysis that follows.…”
Section: Research Articlementioning
confidence: 99%
“…Research into academic performance at an undergraduate level has traditionally identified prior performance as being an important predictor variable. However, more recent studies [3][4][5][6][7][8][9] have found that academic success also depends significantly on the perception of a student regarding their learning environment and how…”
Section: Introductionmentioning
confidence: 99%
“…Factors which have been linked with accounting attainment at tertiary level include entry qualification and general ability (Jackling & Anderson, 1998), prior accounting knowledge (Balwin & Howe, 1982;Bergin 1983;Mitchell, 1988); class size, attributes of the teacher and complexity of the course (Naser & Peel, 1998) and age, tuition and study material (Roos, 2009). Despite the complexity of factors influencing intellectual achievement, a number of studies are pointing to the evidence that gender is associated with academic performance and females are increasingly outperforming males even in the subjects which were traditionally dominated by males (Dayioglu & Turut-Asik, 2004, Gallagher, 2001, University Council and General Board, 2001). …”
Section: Introducing the Studymentioning
confidence: 99%